Profitabilitas, Good Corporate Governance, Pengungkapan Corporate Social Responsibility dan Nilai Perusahaan - Laksmi, Anak Agung Sagung Dewi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2022)
This study aims to obtain empirical evidence regarding the effect of profitability, good corporate governance, and disclosure of corporate social responsibility on firm value. The research was conducted on oil palm plantation companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Purposive sampling is the technique of determining the sample chosen in this study and obtained a sample of 13 companies with a sample of 65 observations. The data analysis technique used is multiple linear regression analysis. Based on the research results obtained evidence, profitability has a positive and significant effect on firm value, good corporate governance has a positive but not significant effect on firm value, and disclosure of corporate social responsibility has a negative and insignificant effect on firm value. Keywords: Profitability; Good Corporate Governance; Corporate Social Responsibility Disclosure; Firm Value.